Unpacking VKC: How gender and age shape the clinical picture - Gaurav Chauhan; Suhita Mathimaaran; Ambika Chandrasekar; Varsha B Chavda; R Mugundhan; Bhaskar Srinivasan; Geetha Iyer; Murlidhar Rajagopalan; Shweta Agarwal (Indian Journal of Ophthalmology)
Purpose: To investigate gender differences in childhood- and adult-onset vernal keratoconjunctivitis (VKC), as well as the variations between these onset groups. Methods: This was a retrospective, observational study (Jan 2015–Dec 2020). Electronic medical records of VKC patients managed by cornea specialists were analyzed based on their age of onset (<16 years for childhood [C-VKC], >16 years for adult [A-VKC]) and gender. Results: Out of 1018 VKC patients, 931 had childhood onset and 87 had adult onset. Both groups showed a male predominance; however, it was slightly less in A-VKC, with a mean follow-up of 28.6 ± 36.2 and 25.03 ± 40.3 months in C-VKC and A-VKC, respectively. A family history of allergies was observed only in C-VKC, with no gender differences. Asthma was more common in C-VKC, while skin allergies were more prevalent in A-VKC. Mixed VKC with Grade 4 severity was the most common in both age groups, with no gender differences in C-VKC; however, the limbal variant was more common in females with A-VKC. The proportion of A-VKC and C-VKC patients who developed complications was similar (P value 0.85). However, the C-VKC group had a significantly higher number of patients with multiple complications (P value 0.0076) as well as those requiring surgical intervention (P value 0.02). Keratoconus was the most common complication in both groups, but limbal stem cell deficiency was significantly higher in A-VKC across genders. Conclusion: Adult-onset VKC is a distinct condition with minor differences and a milder course compared to childhood-onset VKC. Notably, there are no significant gender-based differences in its clinical presentation or complications.